Evaluation of School Based Assessment teacher training programme - Mat Yusoff, Mohd Azmi; Ahmad, Jamil; Mansor, Azlin Norhaini; Johari, Rahayu; Othman, Kamisah; Che Hassan, Norlizah (Scientific Research Publishing, 2016)
This study employed the Kirkpatrick Evaluation Model to assess the reaction of in-service teacher training program on School Based Assessment (SBA) and its contribution towards teacher’s learn- ing (knowledge, skills and attitudes). Kirkpatrick evaluation model has four stages, namely the assessments of reaction, learning (knowledge, skills and attitudes), behavioural and outcomes. This study will discuss the first two stages of assessments that is reaction and learning (knowledge, skills and attitudes). This quantitative survey study used self-developed questionnaires, involving 1200 primary school teachers who had attended the in-service training programme. The respondents were selected randomly from the state of Selangor, Malaysia. The findings of the assessment on reaction which included five sub variables, was on average at a high level. Based on regression analysis: 1) three independent variables (reaction) contributed 21.7 percent to the variances of dependent variables (knowledge); 2) three independent variables (reaction) contributed 19.4 percent to the variances of dependent variable (skills); and 3) three independent variables (reaction) contributed 17.20 percent to the variance of dependent variable (attitudes). These findings suggest that the SBA teacher training program should be continued with strategic improvements to alleviate teachers’ knowledge, skills and attitudes to better improved the implementation of SBA program.